Evaluation of clinical efficacy sparing and standard panretinal laser coagulation of the retina in nonproliferative diabetic retinopathy - O. G. Shilova; I. V. Zapuskalov; S. V. Philippova (Бюллетень сибирской медицины)
We have shown that the classical panretinal laser coagulation is a rather traumatic procedure, damaging all layers of the retina, leadingbto a narrowing of visual fields and decrease the electrical activityof the retina that can impair quality of life. Using sparing laser coagulation is a highly effective metod of prolonged of visual function.